2003
DOI: 10.1242/jeb.00227
|View full text |Cite
|
Sign up to set email alerts
|

Active NaCl absorption across posterior gills of hyperosmoregulatingChasmagnathus granulatus

Abstract: SUMMARYSplit lamellae of posterior gills of Chasmagnathus granulatusadapted to 2.5‰ salinity were mounted in a modified Ussing chamber. With NaCl-saline on both sides of the preparation a transepithelial voltage(Vte) of 4.1±0.5 mV (outside positive) was measured. After voltage-clamping, the negative short-circuit current(Isc) amounted to -142±21 μA cm-2 at a conductance (Gte) of 44±5 mS cm-2. Substitution of either chloride (by nitrate) or sodium (by choline) on both sides of split gill lamellae significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 30 publications
4
40
0
4
Order By: Relevance
“…Each perfusion step allowed for 10 min adjustment of the gill, after which the perfusate was collected for 30 min. To block basolateral K + channels, BaCl 2 was applied basolaterally in the second perfusion step at a concentration of 12 mmol l −1 (Schirmanns and Zeiske, 1994;Riestenpatt, 1995;Riestenpatt et al, 1996;Onken et al, 2003). The inhibitor ZD7288 (4-ethylphenylamino-1,2-dimethyl-6-methylaminopyrimidinium Table 1.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
See 3 more Smart Citations
“…Each perfusion step allowed for 10 min adjustment of the gill, after which the perfusate was collected for 30 min. To block basolateral K + channels, BaCl 2 was applied basolaterally in the second perfusion step at a concentration of 12 mmol l −1 (Schirmanns and Zeiske, 1994;Riestenpatt, 1995;Riestenpatt et al, 1996;Onken et al, 2003). The inhibitor ZD7288 (4-ethylphenylamino-1,2-dimethyl-6-methylaminopyrimidinium Table 1.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…8). In studies to date, the presence of K + channels in the gill epithelium of decapod crustaceans has only been verified by ion flux and shortcircuit current studies on split gill lamellae applying the inhibitors Ba 2+ and Cs + (Onken et al, 1991(Onken et al, , 2003Riestenpatt et al, 1996;Weihrauch et al, 1998Weihrauch et al, , 1999. Because of its similar radius in comparison to K + , Ba 2+ is able to enter the channel pore and bind to the selection filter motif (SF4) domain of the respective K + channels, thereby competing with K + and blocking its binding site more potently because of its dual positive charge (Rossi et al, 2013).…”
Section: Identification Of Cmhcn and Gene Tree Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Application of the electrophysiological Isc method in transport studies on Carcinus gill hemilamella has shown that inward movement of Cl − is mediated by Na + /K + /2Cl − cotransport (Riestenpatt et al, 1996;Onken et al, 2003;Lucu and Towle, 2010). The main generator of this coupled transport is the basolaterally located Na + , K + -ATPase, because specific inhibition of Na + , K + -ATPase by applying ouabain to the basolateral side of the posterior Carcinus gills inhibits the Isc (Siebers et al, 1985;Onken and Siebers, 1992;Riestenpatt et al, 1996;Lucu and Flik, 1999).…”
Section: Introductionmentioning
confidence: 99%